Comparison of the Outcomes of On-Lay and Sub-Lay Mesh Repair in Patients with Ventral Abdominal Wall Hernias: On-Lay and Sub-Lay Repair in Ventral Hernias - Tahir, Ahmad Arsalan; Subhan, Ambareen; Bakhtiar, Nasir; Ishfaq, Muhammad; Farooq, Muhammad; Tayyeb, Muhammad (Pakistan Journal of Health Sciences, 2025)
Hernias of the ventral abdominal wall are a frequent surgical problem that has to be repaired well to reduce complications and recurrence. Objective: To determine which method yields better clinical outcomes. Methods: In two groups of 40 individuals, 80 patients with ventral abdominal wall hernias had the results of Onlay and Sublay mesh repair compared. This prospective study, conducted at Prime Teaching Hospital/Kuwait Teaching Hospital (Peshawar Medical College) from June to December 2024. Data analysis was conducted using SPSS version 23.0 with a significance level of p < 0.05. Results: The mean age of patients was 43.13 ± 11.76 years, among them 62.5% were male. Among this 64% had midline ventral hernias. Patients undergoing Sublay mesh repair experienced significantly lower wound infections (5% vs. 15%, p < 0.05) and less seroma formation (4.61% vs. 20%, p < 0.05) as compared with the Onlay group, notably, the study also found that the duration of hospital stay was significantly longer for the Onlay group compared to the Sublay group (p < 0.05). The sublay technique showed zero recurrence cases (0%), while the On-lay technique had six cases (15%) with statistically significant (p < 0.05). Conclusions: Sublay mesh repair demonstrates distinguishing clinical outcomes over Onlay mesh repair, with lower infection rates, less seroma formation, and shorter hospital stays. The findings suggest that Sublay mesh repair should be preferred for ventral abdominal wall hernias to minimize patient morbidity and improve recovery.